European legislation and incentives programmes for demand side management - Castro, Maria de Fátima (2020)
Energy is now intrinsically linked to technological development, given it powers all such systems. The use of fossil fuels to supply the required energy is causing global environmental and health issues and is impacting on all life forms on the planet. Given increasing energy consumption, anthropogenic greenhouse gas emissions are consequentially increasing. Therefore, it is necessary to replace fossil fuels with renewable energies, biofuels and eco materials and related technologies and to try and find a way to develop sustainable zero emission solutions for all areas including constructions, transport and water resources.A critical and evolutionary way of thinking about the energy (and other resources) demand, management and supply is necessary because there are clear concerns about irreversible impacts to the world and a scarcity of the resources as well. Energy supplies should be mostly or entirely through renewable resources and highly efficient technologies put in place to achieve solution such as nearly Zero Energy Buildings (nZEB).At the same time, all the energy and resource use processes should be optimised in order to maximise the benefits, reduce the costs and promote stakeholders (consumers, companies or governments) network, toward a circular economy. This could be the way to supply the demand without increasing the scarcity of the resources and to simultaneously achieve environmental benefits. Therefore, it should be possible to improve productivity with the same amount of resources, by e.g. maximising the potential of smart grids and heuristically develop solutions with stakeholders.The concept of Demand Side Management (DSM) emerged after the energy crisis and it employs solutions such as reducing the daily peak load. At the same time, creating an educational grid is important to change the established paradigms, in order to promote critical thinking about the wasted resources and thinking holistically about overall consumption. This paradigm shift is changing the market, making it more competiti